Challenges Encountered During Disaster Risk Reduction Initiatives in the Informal Settlements of Nyeri Town - Muriuki, Zachary; Kei, Robert; Muchiri, John Munderu (International Journal of Health Sciences, 2025)
Purpose: This study aimed to assess the challenges encountered during the implementation of DRR initiatives in informal settlements of Nyeri Town, Kenya specifically Majengo Witemere, Ngangarithi kwa Mwaura, Mathari “Transformer,” and Ruring’u Muslim Village. It also explored behavioral factors influencing community engagement using the Theory of Planned Behaviour (TPB). Methodology: A descriptive cross-sectional research design was employed to facilitate analysis of multiple variables related to DRR participation. The study targeted 97,469 residents, from which a stratified sample of 384 respondents was drawn using simple random sampling to ensure representation. Data were collected through structured questionnaires consisting of both closed- and open-ended questions. Ethical approval was secured, and informed consent was obtained from all participants. Findings: Results showed that 43.5% of residents were unaware of ongoing DRR initiatives. Key challenges identified included low community awareness, inadequate funding, weak institutional coordination, and socio-political barriers such as insecure tenure. Demographic factors particularly education and religion were significantly associated with DRR awareness. Application of the TPB revealed that negative attitudes rooted in past institutional failures, weak subjective norms due to fragmented leadership, and limited perceived behavioral control because of poverty and resource scarcity critically undermined community participation in DRR activities. Unique Contribution to Theory, Policy and Practice: The study deepens theory on vulnerability and resilience, informs inclusive urban governance through grassroots integration in DRR, and promotes practical approaches like participatory risk mapping and tailored capacity-building for informal settlements in Nyeri Town.